Determinants of Attractiveness of the Sacred Area of Pakkwarue Wells - Andi Muh Rusdi Maidin; Rajamemang Rajamemang; Wahyudi Putera Yudhie; Wahyuti Wahyuti; Andi Tenri Ulmi; Indah Lestari Yahya (International Journal of Artificial Intelligence Research, 2022)
Sacred Area: The "Pakkawaruwe" Well of Life and Death in Amparita, Sidrap Regency The Tolotang Benteng community has a sacred area, an old well called the "Pakkawaruwe" well, which is a legacy of their founder La Panaungi. They believe the well water can bring success in their lives. This study aims to explain and analyze the influence of attraction to the sacred area through business success, peace of life and cultural preservation. The population in this study were the participants, especially the Tolotang Benteng Community, which amounted to Â± 11,000 people in South Sulawesi Province spread across 4 districts / cities including Sidrap, Pinrang, Pare-Pare, and Makassar.The sample used in this study was 180 respondents, using NonProbability Sampling, namely Purposive Sampling or this technique, a researcher can provide an assessment of who should participate in a study. A researcher can implicitly choose a subject that is considered representative of a population. This means that the sampling technique is generally used by the media when asking for opinions from the public about something. The media will choose which subjects are considered to represent the public. As for determining the number of samples used, the researcher used the Slovin Formula with a combination of mix methods combining quantitative and qualitative approaches which were used sequentially in this study. Data were obtained through observation, interviews, questionnaires, and documentation. The analysis technique used for hypothesis testing is path analysis using the help of the SPSS For Windows program. The results showed that the attraction indirectly (indire effect) had a significant effect on business success. Furthermore, the attraction directly (direct effect) has an effect, and is significant to the sacred area, and business success both directly and indirectly (direct and indirect effect) has an effect and is significant to the sacred area with a coefficient of determination of 82%. This study they recommend that religious harmony that runs well is maintained and maintained so that there is no horizontal conflict between fellow Amparita villagers Sidenreng rappang district (Sidrap).